2019
DOI: 10.1136/bmjopen-2018-028537
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of the HIP fracture Accelerated surgical TreaTment And Care tracK (HIP ATTACK) Trial: a protocol for an international randomised controlled trial evaluating early surgery for hip fracture patients

Abstract: IntroductionAnnually, millions of adults suffer hip fractures. The mortality rate post a hip fracture is 7%–10% at 30 days and 10%–20% at 90 days. Observational data suggest that early surgery can improve these outcomes in hip fracture patients. We designed a clinical trial—HIP fracture Accelerated surgical TreaTment And Care tracK (HIP ATTACK) to determine the effect of accelerated surgery compared with standard care on the 90-day risk of all-cause mortality and major perioperative complications.Methods and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…A multicenter quality improvement study from 2018, comparing a care pathway with usual admission and care, found no differences in mortality or functional outcome (Panella et al 2018). An RCT on preoperative waiting time is being conducted and the results from that trial will probably elucidate this question (Borges et al 2019). Reduced preoperative waiting time may reduce the LOS, but we believe that the reduced LOS in the HFU was mainly due to improved capacity in the municipal health services (Table 3) (Monkerud and Tjerbo 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter quality improvement study from 2018, comparing a care pathway with usual admission and care, found no differences in mortality or functional outcome (Panella et al 2018). An RCT on preoperative waiting time is being conducted and the results from that trial will probably elucidate this question (Borges et al 2019). Reduced preoperative waiting time may reduce the LOS, but we believe that the reduced LOS in the HFU was mainly due to improved capacity in the municipal health services (Table 3) (Monkerud and Tjerbo 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The HIP ATTACK trial is a multinational, parallel-group superiority randomised controlled trial of patients who present to the emergency department with a hip fracture requiring surgical repair. The main trial protocol is described elsewhere 6. Briefly, patients who sustained a hip fracture were randomly allocated (1:1) to receive accelerated medical assessment and surgical repair (with the goal of having the surgery performed within 6 hours after the orthopaedic diagnosis) or usual care (where a repair typically occurs 24–48 hours after diagnosis).…”
Section: Methods and Analysismentioning
confidence: 99%
“…Patients were recruited from the emergency department. Eligibility criteria for the main HIP ATTACK trial are fully detailed in the published protocol 6. Eligible patients included those aged 45 years or older diagnosed with a hip fracture with a low-energy mechanism (eg, a fracture sustained from a fall not beyond standing height) requiring surgery.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations